Clinical Effectiveness of Tislelizumab With Gemcitabine/Cisplatin Versus Gemcitabine/Cisplatin Alone as Adjuvant Therapy for High‐Risk Muscle‐Invasive Urothelial Carcinoma: A Real‐World Study - Yanjun Wang; Kaihua Zhong; Xingliang Tan; Qianghua Zhou; Lijuan Jiang; Kai Yao; Zhiming Wu (Cancer Medicine)
ABSTRACT Background Muscle‐invasive urothelial carcinoma (MIUC) is a highly aggressive cancer associated with poor prognosis. Despite advancements in treatment, the optimal therapeutic approach remains unclear. Immune checkpoint inhibitors, when added to chemotherapy, have shown promise in improving patient outcomes. Aims This study aimed to evaluate the efficacy and safety of adjuvant tislelizumab combined with gemcitabine/cisplatin (Tisle+GC) compared to GC alone in patients with high‐risk MIUC. Materials & Methods We conducted a retrospective analysis of 117 patients with histologically confirmed pT3/4 and pN+ MIUC treated at our center between October 2016 and March 2023. Eligible patients received either Tisle+GC or GC alone, excluding those with prior neoadjuvant therapy. We compared disease‐free survival (DFS), overall survival (OS), and treatment‐related adverse events (AEs) between the two groups using Cox proportional hazards models and Kaplan–Meier estimates. Results The Tisle+GC group showed significantly longer median DFS (19.08 vs. 9.06 months, HR = 0.114, p < 0.001) and OS (20.07 vs. 10.63 months, HR = 0.083, p = 0.026) compared to the GC group. Nerve tract invasion was identified as a significant predictor of poor outcomes (HR = 22.1, p = 0.003). Both groups experienced manageable grade 1–2 immune‐related AEs, with pruritus being the most common, followed by liver function abnormalities and thyroid disturbances. Nonhematologic toxicities in the Tisle+GC group included elevated aspartate aminotransferase and hyponatremia, while the GC group mainly reported vomiting. No treatment‐related fatalities occurred. Discussion The addition of tislelizumab to GC chemotherapy significantly improved both DFS and OS in high‐risk MIUC patients. The safety profile was manageable, with immune‐related AEs being predictable and not life‐threatening. The findings support the potential of Tisle+GC as an effective adjuvant therapy. Conclusion Tisle+GC is a promising adjuvant treatment for high‐risk MIUC, offering improved survival outcomes with a manageable safety profile. Further prospective studies are needed to confirm these results and establish the long‐term benefits of this combination therapy.